EDUKASI LITERASI DAN INKLUSI LEMBAGA KEUANGAN SYARIAH DI SMK HIDAYATUT THALIBIN JAKARTA - Sufyati HS; Dipateruna Awaloedin (Bajang Institute, 2021)
In the context of Islamic finance, it is necessary to provide adequate understanding to the public regarding financial issues such as Islamic banking and non-bank financial services institutions, products, contracts and Islamic financial services. The purpose of community service is to introduce Indonesian youth, especially students of Hidayatut Thalibin Vocational High School, one of the schools with an Islamic concept, namely providing literacy education and inclusion of Islamic financial institutions. The implementation method consists of three stages. The first stage is an introduction to the theory of Islamic and non-Islamic financial institutions. The second stage is counseling and simulation of Islamic and non-Islamic banking products and contracts. The last stage is evaluation, which is to determine the level of students' understanding of Islamic banking and non-Islamic banking. The results of this educational activity showed that the students gained sufficient knowledge of the elements of theory and application based on the post-test given regarding Islamic banking products and contracts. The implication of this educational activity is that youth are expected to contribute to the development of Islamic financial institutions in Indonesia